Ownership Transformations of State-owned Enterprises with Special Consideration of Direct Privatisation in Poland in the Years 2004-2008; Przekształcenia własnosćiowe polskich przedsiebiorstw panśtwowych ze szczegoĺnym uwzglednieniem prywatyzacji bezposŕeniej w latach 2004-2008 - Marzena Papiernik-Wojdera; Agnieszka Matuszewska-Pierzynka (Comparative Economic Research. Central and Eastern Europe, 2010)
The main goal of this article is defining the present state of the process of ownership transformations in Polish state-owned enterprises and progress in this process during the last five years. The main research hypothesis formulated in the article was verified by means of an analysis of data published by the Central Statistical Office concerning the number of state-owned enterprises covered by ownership transformations. The accepted scope of this article encompassed: concepts, objectives and methods of ownership transformation in Polish state-owned enterprises, as well as different issues connected with direct privatization by means of passing state-owned enterprises for use against payment to employee-owned companies. – – Zasadniczym celem artykułu jest okresĺenie biezȧcego stanu procesu przekształcenẃłasnosćiowych polskich przedsiebiorstw panśtwowych oraz jego przebiegu w ciagu ostatnich pieciu lat. Weryfikacja sformułowanej w opracowaniu głoẃnej hipotezy badawczej została dokonana w oparciu o analize danych Głoẃnego Urzedu Statystycznego dotyczacych liczby przedsiebiorstw panśtwowych objetych procesem przekształcenẃłasnosćiowych. W konteksćie przyjetego zakresu tematycznego przedstawiono pojecie, cele i metody przekształcenẃłasnosćiowych polskich przedsiebiorstw panśtwowych oraz problematyke zwiazana z prywatyzacja bezposŕednia realizowana w drodze oddania przedsiebiorstwa panśtwowego do odpłatnego korzystania spoĺce pracowniczej.
Keywords: 330